Determinants of the Size of Private Sector Credit Disbursement in Ghana - Idun, Anthony Adu-Asare; Agyei, Samuel Kwaku; Bainn, Soraya (Asian Development Policy Review, 2020)
The paper examines the antecedence of the size of private sector credit disbursement in Ghana using symmetric and asymmetric ARDL processes. We find that the treasury bill rates have both a direct and an indirect impact on the amount of credit channelled to the private sector with positive shocks dominating the stimulating effect of the treasury bill rate. Similarly, negative shocks in the average lending rates have a detrimental effect on the credit to the private sector which supports the view that banks use interest rates to ration credit. Also, the saving rates have a direct and indirect effect on private sector credit but positive shocks in the savings rate have a detrimental effect on the amount of credit to the private sector. Moreover, we found a dominance positive effect of the shocks in foreign currency deposits on private sector credit disbursement. Finally, a rise in crude oil prices induces private sector allocation in Ghana even though the effect of oil prices on credit appears mixed.